Ownership structure and voluntary disclosure in corporate annual reports of Malaysian listed firms - Ho, Poh-Ling; Tower, Greg (Virtus Interpress, 2011)
This paper examines the impact of ownership structure on the voluntary disclosure in the annual reports of Malaysian listed firms. The result shows that there is an increase in the extent of voluntary disclosure in Malaysian listed firms over the eleven-year period from 1996 to 2006. Ownership concentration consistently shows positive association with voluntary disclosure. Firms with higher foreign and institutional ownership have a significantly positive association with voluntary disclosure levels while firms with family ownership exhibit lower voluntary disclosure. Consistent with agency theory, different ownership structures have varied monitoring effects on agency costs and clearly influence firm’s disclosure practices. The findings provide insights to policy makers and regulators in their desire to increase transparency and accountability amidst the continual enhancement of corporate governance. The findings provide evidence that optimized ownership structure in any jurisdiction should be considered in any regulatory process that seeks to improve transparency.